Urethral prolapse- case report and photographs - Mahale, Arun R.; Sakhare, Anil P. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
A report on menopausal age group urethral prolapse with illustrative photographs, its treatment and related literature review is presented.